Alien plant species list and distribution for Camdeboo National Park, Eastern Cape Province, South Africa - Mmoto L. Masubelele (Koedoe: African Protected Area Conservation and Science, 2009)
Protected areas globally are threatened by the potential negative impacts that invasive alien plants pose, and Camdeboo National Park (CNP), South Africa, is no exception. Alien plants have been recorded in the CNP since 1981, before it was proclaimed a national park by South African National Parks in 2005. This is the first publication of a list of alien plants in and around the CNP. Distribution maps of some of the first recorded alien plant species are also presented and discussed. To date, 39 species of alien plants have been recorded, of which 13 are invasive and one is a transformer weed. The majority of alien plant species in the park are herbaceous (39%) and succulent (24%) species. The most widespread alien plant species in the CNP are Atriplex inflata (= A. lindleyi subsp. inflata), Salsola tragus (= S. australis) and cacti species, especially Opuntia ficus-indica. Eradication and control measures that have been used for specific problematic alien plant species are described. Conservation implications: This article represents the first step in managing invasive alien plants and includes the collation of a species list and basic information on their distribution in and around the protected area. This is important for enabling effective monitoring of both new introductions and the distribution of species already present. We present the first species list and distribution information for Camdeboo National Park.